Acoustic radiation-based optimization of the placement of actuators for active control of noise transmitted through plates. (15th January 2021) - Wrona, Stanislaw; Pawelczyk, Marek; Cheer, Jordan
Graphical abstract: Highlights: A new approach for the optimization of the actuators placement is presented. A model of acoustic radiation is introduced into the optimization process. New cost functions are formulated to focus on modes that are acoustically-relevant. This enables an increase in the controllability measure of more than 5 dB. Such increase is comparable to that achieved by doubling the number of actuators. Abstract: Active Structural Acoustic Control (ASAC) is mostly performed using a passive noise barrier, vibration actuators, sensors and a control system. ASAC reduces or alters the vibration of the barrier structure in a way that blocks the noise propagation through it. However, it is crucial that the actuators are appropriately arranged to be able to effectively control the vibration of the barrier. If the actuators were not optimally arranged, then certain modes of the structure may be uncontrollable, or require a very high control effort. Hence, the locations of the actuators should be determined by a careful optimization process employing a model of the structure. A common approach is to maximize the controllability of the system over a defined frequency range of operation. However, such an optimisation procedure often results in a solution that considers numerous vibration modes, only some of which are acoustically-relevant. That is, certain structural modes may vibrate considerably, but their contribution to the noise transmission and radiation would be negligible. Therefore, in the presented research a new acoustic radiation-based approach to the optimisation of the arrangement of actuators is proposed. A model of acoustic radiation is introduced and new cost functions are formulated to focus on modes that strongly contribute to noise transmission or radiation by the noise barrier. For the considered system, this enables an increase in the controllability measure of more than 5 dB for acoustically-relevant modes, which is similar to the level of improvement achieved when the number of actuators is doubled.